2004
DOI: 10.1159/000076455
|View full text |Cite
|
Sign up to set email alerts
|

Social Support and the Persistence of Complaints in Chronic Fatigue Syndrome

Abstract: Background: Several studies suggested that the surroundings of chronic fatigue syndrome (CFS) patients are of importance in the persistence of complaints. Contrary to what was expected, participation in support groups has not led to clinical improvement. The purpose of the present study was to describe social support in CFS patients as compared with other fatigued and non-fatigued groups. Further, changes in social support and the influence of social support on the course of CFS over a period of more than 1 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 17 publications
2
55
0
3
Order By: Relevance
“…The associations of prolonged difficulties and social support with outcome are in line with studies among patients with chronic fatigue syndrome, showing that negative interactions or insufficient support contribute to the persistence of symptoms, 31 and that negative or serious difficulties were more frequent in the months preceding the onset of chronic fatigue syndrome. 32,33 Furthermore, enjoying daily activities was univariately associated with a positive outcome in the current study, while the number of life events was not associated with a negative outcome.…”
Section: E106supporting
confidence: 83%
“…The associations of prolonged difficulties and social support with outcome are in line with studies among patients with chronic fatigue syndrome, showing that negative interactions or insufficient support contribute to the persistence of symptoms, 31 and that negative or serious difficulties were more frequent in the months preceding the onset of chronic fatigue syndrome. 32,33 Furthermore, enjoying daily activities was univariately associated with a positive outcome in the current study, while the number of life events was not associated with a negative outcome.…”
Section: E106supporting
confidence: 83%
“…The results of this study suggest that the psychological and social support required by patients may vary depending on their level of fatigue. This study is aligned to the work of others who have suggested that interventions that strengthen the social support network of cancer patients may improve health outcome by protecting them from disease-related stress (Karakoc & Yurtsever, 2010;House, 2011;Uchino, 2004;Prins et al, 2004).…”
Section: Discussionsupporting
confidence: 62%
“…Furthermore, with 112 included patients (105 starting), the current study is one of the largest RCTs of allo-HSCT and physical exercise. The control group had the same dose of social contact, a key consideration when studying cancer-related fatigue 35 and QoL 36 in the context of HSCT. 37 Our study demonstrates that a partly supervised exercise intervention that is initiated before HSCT and continues after discharge significantly reduced cancer-related fatigue and improves the secondary outcome parameters physical capacity, functioning, anger/ hostility, pain, and global distress, which are the most common and impairing adverse effects of allo-HSCT besides GVHD.…”
Section: Discussionmentioning
confidence: 99%